Generic melt compounding strategy using reactive graphene towards high performance polyethylene/graphene nanocomposites. (16th June 2019) - Wang, Bin; Peng, Dan; Lv, Ruihua; Na, Bing; Liu, Hesheng; Yu, Zhong
Abstract: A reactive melt compounding technique using vinyl-grafted graphene was exploited for mass production of PE/graphene nanocomposites. The as-extruded nanocomposites had good filler dispersion and interfacial interaction, as evidenced by transmission electron microscopy and linear rheological results. Compared to neat PE, the nanocomposites with 1.0 wt% graphene showed one order of magnitude and nearly two orders of magnitude increment in complex viscosity and storage modulus at low frequency (<0.1 Hz), respectively. Due to strong interfacial interaction, the graphene nanoplatelets act as nucleating agents to increase the crystallization temperature of PE, but hinder the following growth of crystallites. As a result, mechanical properties and barrier to oxygen of the nanocomposites were obviously improved. This work provides a facile strategy for mass production of high-performance polyolefin/graphene nanocomposites and may be other polymer/graphene nanocomposites.